Chemistry, College Level. Annotated Bibliography of Tests - Educational Testing Service, Princeton, NJ. Test Collection; Educational Testing Service, Princeton, NJ. Test Collection ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Most of the 30 tests cited in this bibliography are those of the American Chemical Society. Subjects covered include physical chemistry, organic chemistry, inorganic chemistry, analytical chemistry, and other specialized areas. The tests are designed only for advanced high school, and both bachelor/graduate degree levels of college students. This document is one in a series of topical bibliographies from the Test Collection (TC) at the Educational Testing Service (ETS) containing descriptions of more than 18,000 tests and other measurement devices prepared by commercial publishers, teachers, educational institutions, professional associations, departments of education, counselors, etc. Each description contains the following basic information: TC Accession Number (a six-digit identification number assigned by the Test Collection); the title of the instrument; personal or institutional author; year of publication or copyright; availability source; grade level for which test is suitable; age level for which test is suitable; and abstract. Other information, which is provided when known, includes subtests, number of test items, and time required to complete the test. Information on accessing the Test Collection via Internet concludes the document. (CRW)
ERIC Note: Supersedes April, 1989 edition.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement Tests; Annotated Bibliographies; Certification; Chemistry; College Entrance Examinations; Equivalency Tests; Higher Education; Mastery Tests; Science Achievement; Science Tests; Student Evaluation; Test Bibliographies -- Test Collection (Educational Testing Service); Reference Materials, Bibliographies